Identification of sources of job stress: a study among officers and supervisors. (30th July 2019) - Sidhu, Amanpreet Kaur; Singh, Harwinder; Virdi, Sandeep Singh; Kumar, Raman
The purpose of the present paper is to identify the major sources of job stress among PSPCL and PSTCLs employees. A sample of 249 PSPCL and PSTCLs employees was used in the study. Ten factors determined the model: working environment, performance assistance, personal growth, future perspective, control scale, job requirement, workload, responsibility, moment demand and satisfaction. Total of 34 variables were used for confirmatory factor analysis (CFA), to carry out many aspects of job stress. It was found that moment demand is the major contributing factor to job stress. Training needs, working conditions and less salary are the key variables to generate job stress. These variables can assist in maintaining job stress in PSPCL and PSTCL. The objective of this research paper is to examine, the sources of stress among officers and supervisors, under Punjab State Power Corporation Limited (PSPCL) and Punjab State Transmission Corporation Limited (PSTCL).